A survey of doctoral supervisors in South Africa - Mouton, Johann; Boshoff, Nelius; James, Megan (South African Journal of Higher Education, 2016)
South African universities receive a direct monetary reward for the number of doctoral graduates produced. As a result there has been a steady increase in numbers in recent years (from 977 in 2004 to 1,878 in 2012), with obvious implications for doctoral supervision. Against this background a web-based survey of 331 doctoral supervisors at South African universities was conducted in 2011. The findings are discussed with reference to four themes: the burden of numbers, the nature of the PhD, screening and selection of doctoral candidates, and supervisory styles. The main conclusion is that many doctoral supervisors in South Africa conduct their supervision under less-than-optimal conditions. Increasing student numbers, demands for constant monitoring and accountability, the pressure of throughput rates and efficient completion together with moderate-to-poor quality students, has resulted in a situation where doctoral supervision has become a challenging and highly stressful undertaking.